INVESTMENT CRITERIA SET BY VENTURE CAPITALISTS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
Different funders, like bankers, business angels or venture capitalists, put the accent on various investment criteria while making investment decisions. Entrepreneurs need to be familiar with these criteria or different requirements of potential investors in order to adjust their business plans. Motivated by the phenomenon of venture capital, numerous researchers worldwide are trying to identify the venture capitalists’ investment criteria. Despite the large number of studies, there is still no unambiguous answer to what the key venture capitalists’ investment criteria are. This paper provides an overview of research about investment criteria set by different suppliers of capital with a special emphasis on venture capitalists’ investment criteria. The most used VCs’ investment criteria discussed in the literature are identified and analysed in order to provide a new set of VC investment criteria. Keywords: Venture capital, venture capitalists, entrepreneur, investment criteria